2016
DOI: 10.1038/srep36346
|View full text |Cite
|
Sign up to set email alerts
|

Metal-coupled folding as the driving force for the extreme stability of Rad50 zinc hook dimer assembly

Abstract: The binding of metal ions at the interface of protein complexes presents a unique and poorly understood mechanism of molecular assembly. A remarkable example is the Rad50 zinc hook domain, which is highly conserved and facilitates the Zn2+-mediated homodimerization of Rad50 proteins. Here, we present a detailed analysis of the structural and thermodynamic effects governing the formation and stability (logK12 = 20.74) of this evolutionarily conserved protein assembly. We have dissected the determinants of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
131
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(137 citation statements)
references
References 57 publications
5
131
1
Order By: Relevance
“…However, in the case of Hk27, Hk31, and Hk45, the formation of CdHk (ML) complexes also occurs. The largest difference in stability between ML and ML 2 complexes is observed for Hk27, which is reflected by two visible inflection points, whereas the Hk6, Hk10, and Hk14 peptides demonstrate the strongest tendency to form only dimeric species, similarly to the study of Zn II complexes (Figure and Figure S2, Supporting Information). In the case of Hk130, the CD spectra changes slightly (Figure a), which complicates stoichiometric analysis.…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…However, in the case of Hk27, Hk31, and Hk45, the formation of CdHk (ML) complexes also occurs. The largest difference in stability between ML and ML 2 complexes is observed for Hk27, which is reflected by two visible inflection points, whereas the Hk6, Hk10, and Hk14 peptides demonstrate the strongest tendency to form only dimeric species, similarly to the study of Zn II complexes (Figure and Figure S2, Supporting Information). In the case of Hk130, the CD spectra changes slightly (Figure a), which complicates stoichiometric analysis.…”
Section: Resultssupporting
confidence: 55%
“…To assess if the structure and stability of Cd II complexes rely on a similar structural basis to that of Zn II , we used a series of zinc hook (Hk) peptides ranging in length from 4 to 130 amino acid residues (Hk4–Hk130) (Figure ). Peptide Hk45 has been recognized as a fragment which, as a Zn II complex, possesses all residues that form intermolecular contacts and contains both α‐helical and β‐hairpin regions of the domain . Peptides Hk4, Hk6, Hk10, and Hk14 were used to investigate metal‐coupled formation of the β‐hairpin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We showed that cysteines of certain CXXC motifs in zinc binding sites possess significantly different acid-base properties due to the presence of S⋯H–N hydrogen bonds [36,89]. Such hydrogen bonds exist in MTs [9,90,91] and could be responsible for the observed structure of T despite the apparent lack of a defined overall structure of the protein.…”
Section: Zn2+ Affinity For Human Metallothioneinmentioning
confidence: 99%